2007
DOI: 10.1002/glia.20592
|View full text |Cite
|
Sign up to set email alerts
|

Microglia induce neurotoxicity via intraneuronal Zn2+ release and a K+ current surge

Abstract: Microglial cells are critical components of the injurious cascade in a large number of neurodegenerative diseases. However, the precise molecular mechanisms by which microglia mediate neuronal cell death have not been fully delineated. We report here that reactive species released from activated microglia induce the liberation of Zn(2+) from intracellular stores in cultured cortical neurons, with a subsequent enhancement in neuronal voltage-gated K(+) currents, two events that have been intimately linked to ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 63 publications
1
53
0
Order By: Relevance
“…Next, to determine whether inhibition of CaMKII was neuroprotective, we transfected neurons with a plasmid encoding CaMKIIK42R (or empty vector) in addition to a luciferase-expressing plasmid used to assess viability in transfected cells (54). Neurons were later exposed to activated rat microglia (55), which we showed to be a powerful inducer of Zn 2+ -dependent, Kv2.1-mediated injury via peroxynitrite production (56). We observed that neurons expressing CaMKIIK42R were significantly protected from microglia toxicity compared with vector-expressing cells (Fig.…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neumentioning
confidence: 99%
“…Next, to determine whether inhibition of CaMKII was neuroprotective, we transfected neurons with a plasmid encoding CaMKIIK42R (or empty vector) in addition to a luciferase-expressing plasmid used to assess viability in transfected cells (54). Neurons were later exposed to activated rat microglia (55), which we showed to be a powerful inducer of Zn 2+ -dependent, Kv2.1-mediated injury via peroxynitrite production (56). We observed that neurons expressing CaMKIIK42R were significantly protected from microglia toxicity compared with vector-expressing cells (Fig.…”
Section: Injurious Oxidant Exposure Leads To Camkii Activation In Neumentioning
confidence: 99%
“…When stimulated during brain injury, the overactivation and dysregulation of microglia can compound neuronal damage by releasing neurotoxic cytokines, matrix metalloproteinases, and NO and superoxide (O (52). Further, microglia-derived reactive oxygen and nitrogen species (ROS and RNS) triggered the well-characterized apoptotic signalregulating kinase-1 (ASK1)=p38-dependent, Kv2.1-mediated K þ current surge (52).…”
Section: Zinc-dependent Signaling In Neuronal Deathmentioning
confidence: 99%
“…Further, microglia-derived reactive oxygen and nitrogen species (ROS and RNS) triggered the well-characterized apoptotic signalregulating kinase-1 (ASK1)=p38-dependent, Kv2.1-mediated K þ current surge (52). When these studies were repeated in neurons overexpressing MT III, thereby chelating free Zn 2þ , the K þ current surge and neuronal cell death were markedly reduced (52). Thus, microglial activation can lead to a neuronal free Zn 2þ rise and Zn 2þ -dependent neuronal cell death.…”
Section: Zinc-dependent Signaling In Neuronal Deathmentioning
confidence: 99%
“…Activated microglia produce inflammatory mediators including nitric oxide (NO), superoxide, and proinflammatory cytokines, leading to a robust neuroinflammatory response. 4,5) NO produced by inducible NO synthase (iNOS) rapidly reacts with superoxide to form a highly toxic product, peroxynitrite. This product has been shown to exaggerate neuropathological injury.…”
mentioning
confidence: 99%